Revisiting the one-minute paper: Personal reflections, student engagement and assessing the assessment - MANIATES, Rebecca Pappert (Institutional Knowledge at Singapore Management University, 2022)
The one-minute paper (OMP) is a popular one-shot session assessment which often consists of asking two questions: 1 . What is the most important thing you learned today? 2 . What questions do you still have? Although simple, each question has a purpose. The first is broad, focusing on the importance of concepts learned (Chizmar & Ostrosky, 1998), and promotes active learning and reflection (Stead, 2005). The second assesses the progress of the learning process and where support is still needed (Chizmar & Ostrosky, 1998).Although studies show the OMP is effective when assessing student knowledge before and after one-shot sessions (Wolstenholme, 2015) and when assessing outcomes (Choinsky & Emanuel, 2006), others suggest it is not appropriately robust to assess student learning (Sobel & Wolf, 2011). This project proposes that the OMP is still relevant as a method for better understanding student learning through analysis of student reflections. This project also demonstrates how the OMP encourages meaningful student engagement beyond the one-shot classroom.OMPs were collected from 340 students across 10 one-shot sessions from January through April 2021 . The analysis uses a method developed by Wolstenholme (2015) to code student responses based on five response categories to find evidence of student reflection. The analysis identifies evidence of learning, application of concepts, as well as deep thinking. Through thoughtful evaluation of student responses, the instructor can identify strengths in classroom, as well as concepts needing more attention to fill gaps in student knowledge and awareness.Using the OMP as an engagement tool beyond the classroom is another contribution of this project. The results show communication with students at the class level, as well as through personal responses to queries, helps to improve student confidence, raise awareness of expertise and library services, as well as extend learning beyond the boundaries of the one-shot session.